THE INFLUENCE OF PROMOTION AND PRODUCT QUALITY ON THE DECISION TO PURCHASE ECO PRINT BATIK DANAU TELUK DISTRICT - Taufiq Akbar Dewi Firdaus; Ratih Kusumastuti; Derist Touriano (CV. Adiba Aisha Amira, 2025)
Hypotheses are the answer to formulating a research problem, which means asking questions (Sugianto, 2016: 93). The research hypotheses were established based on the problem (1) Promotions, quality of batik products and sales decisions are believed to favor idol batik; (2) Batik Ecoprint Danau Teluk, we hypothesize that promotions and product quality have a significant influence on purchasing decisions is a small business specializing in the production and marketing of batik handicrafts. This study uses quantitative methods that focus on Batik Ekoprint consumers. The multiple linear regression output used in the study can be expressed as Y = 2.071 +1.423 X1 + 0.434 X2 with an adjusted R square (R2) of 0.836. This means that 16.4% of the variance in the dependent variable (Y) can be: Due to the independent variables (X1 and X2). The test result (component) of the regression model shows a significant value of 0.617 when the coefficient is 0.502 and the coefficient is 1.660. 0.502 and above; In 1,660, promotions (X1) are determined to have a significant impact on purchase decisions. H0 is rejected and Hi is accepted.